IMPROVING VOCABULARY MASTERY THROUGH COOPERATIVE LEARNING METHOD: TGT (TEAMS GAME TOURNAMENT) - Hasanah, Roslatul; Sholichah, Norma Ita (Universitas Dharmawangsa Medan, 2025)
This study aims to improve vocabulary mastery among 4A students at MI Nurul Hidayah through the Teams Game Tournament (TGT) cooperative learning method. This study was conducted using a Classroom Action Research (CAR) approach and consisted of two cycles to evaluate the impact of TGT on student engagement and vocabulary mastery. Initial observations showed that students had difficulty mastering vocabulary due to traditional memorization methods, which resulted in low engagement and achievement. In the first cycle, only 44.44% of students obtained an average score of 66.66, while the success criterion in this study was that 80% of students could obtain an average score of 70. Therefore, further research was needed in the next cycle. Adjustments were made in the second cycle, including the incorporation of movements and interactive activities, which resulted in increased student participation and vocabulary test scores, with 83.33% of students achieving an average score of 80.55. In this cycle, the success criteria were met, so the study was terminated in the second cycle. These findings indicate that TGT is an effective strategy for improving vocabulary mastery and creating a dynamic and engaging learning environment. This study contributes to the existing literature on cooperative learning methods in elementary education and emphasizes the importance of innovative teaching approaches.